Three Top Canadian and Personal Health Concerns of a Random Sample of Nova Scotian Women - Davidson, Karina W. (Can J Public Health, 2001)
We sought to understand the subjective reports of women’s health concerns. A randomly dialled telephone survey was conducted resulting in a sample of 458 women (Caucasian/European = 302, Native/ Aboriginal = 81, Black = 75), aged 18–81. Women were asked in an open-ended format to list their three top health concerns for themselves and then for Canadian women. Responses were recorded verbatim and categorized into one of nine mutually exclusive health concern categories. The three main health concerns for Canadian women were: Psychosocial Issues, Other Specific Illnesses, and Cancer. The three most important personal health concerns were Psychosocial Issues, Other Specific Illnesses, and Heart and Related Diseases. Few ethnic differences were noted. Results suggest that it is important to recognize and attempt to alleviate health concerns about stress and depression, which are not usually considered as being major health problems by health care professionals.